Mapeamento de QTL's para componentes associados a biomassa em cana-de-açúcar - Cruz, Malú Del Socorro Carranza (2023)
Sugarcane (Saccharum spp.) is one of the world's main agro-industrial crops, with about 124 countries producing sugar. During the 2021/2022 season, a global increase of 0.53% was observed, producing 181 million tons. Over the past 20 years in Peru, sugarcane has shown visible growth, with 2006 marking the year when growth began to accelerate. In 2021, production reached 12.309 million tons of cane, of which 79% were used for sugar production. Its importance lies in its use for sugar and ethanol production. Sugarcane is characterized as an autopolyploid with a high level of ploidy and aneuploidy in its gigagenome. The objective of this project was the identification and mapping of QTLs (quantitative trait loci) for agro-industrial traits in sugarcane, constructing a genetic map to identify genomic regions associated with plant height and diameter. The study population was developed by the Sugarcane Breeding Program at the Federal University of São Carlos (UFSCar). A total of 238 genotypes, derived from the cross between SP81-3250 and RB925345, were genotyped using SNP markers obtained through GBS (Genotyping by Sequencing) and evaluated in the field for plant height and diameter. By aligning the GBS sequences with the genomes of Sorghum and Saccharum spontaneum, approximately 152,000 and 250,000 variants, respectively, were identified. From this total, after all filtering steps and segregation analysis, 15,795 SNP markers were used to construct the genetic map. In addition, 285 gel-based marker fragments were also suitable for genetic map construction. A total of 2,016 markers were included in the linkage map, which consisted of 221 linkage groups, spanning 5,282 cM with a density of 3.06 cM.The mapping analysis identified two QTLs, one for plant height and another for plant diameter. For plant height, the QTL was located in linkage group 11, exhibited a 1:1 segregation pattern, and explained 6.38% of the observed phenotypic variation. For plant diameter, the QTL was located in linkage group 53, exhibited a 1:2:1 segregation pattern, and explained 4.59% of the observed phenotypic variation.